A population genetic analysis of the nematode Strongyloides stercoralis in Asia shows that human infection is not a zoonosis from dogs - Yuchen Liu; A. H. M. Raihan Sarker; Banchob Sripa; Sirikachorn Tangkawattana; Virak Khieu; William Nevin; Steve Paterson; Mark Viney (Proceedings of the National Academy of Sciences, 2025)
Gut nematode worms are important parasites of people and other animals. The parasitic nematode Strongyloides stercoralis infects an estimated 600 million people worldwide and is one of the soil-transmitted helminthiases, a WHO-defined neglected tropical disease. It has long been suggested that human S. stercoralis infection may be a zoonosis from dogs. We investigated this by whole genome sequence analysis of S. stercoralis from sympatric human and dog populations in Asia. We find that human- and dog-derived S. stercoralis have genetically distinct nuclear genomes, but we also find evidence of rare cross-infection. Analysis of the S. stercoralis mitochondrial genome reveals evidence of historical introgression between human- and dog-derived parasites. Based on these data, we suggest that S. stercoralis was originally a parasite of canids, that began to infect humans when people domesticated dogs, since when human- and dog-derived parasites have differentiated, but have not become separate species.